Equipe multiprofissional e educação omnilateral: a experiência nas escolas municipais de Foz do iguaçu de 2006 a 2016 - Craveiro, Adriéli Volpato (2019)
Consider as different expressions of the "social issue" that affect social relations prohibited in schools in Brazil, in different situations and in which these spaces are heard with professions other than those linked to the teaching profession, among which, Social Work and Psychology. However, an insertion of these categories in the school's professional team is permitted due to position differences. In the year 2006 to 2017, a municipal education network in Foz do Iguaçu counted on the Building the Citizenship Program, which enabled a multiprofessional performance in municipal schools. Seeking to deepen this discussion, this article has as a general objective to analyze the insertion of the Multiprofessional Team in the municipal schools of Foz do Iguaçu, between the years 2006 to 2016 and its possible contribution in fostering school education guided by a unilateral educational perspective. In 2016, we worked in the 23 (twenty-three) professional program. It has an interview granted to a coordinating researcher, a physiotherapist, 02 (two) speech therapists, 05 (five) psychologists and 07 (seven) social workers. However, as the research resource was developed around Social Work and Psychology professionals, they were analyzed for an understanding of the Multiprofessional Team's performance, only as interviews with Social Work and Psychology professionals. The interviews carried out and the other professionals served to understand the Program, its history and its formation. To complement the information brought during the interviews, an interview was also conducted with the first coordinator of the Building the Citizenship Program. It is a qualitative research, which is to collect the data used in the interviews that were transcribed and later analyzed by the Content Analysis methodology. For better understanding or proposed theme, bibliographical and documentary research was also carried out. The results pointed out for the Building the Citizenship Program, throughout its history, demonstrate the importance of multiprofessional and intersectoral work developed in the school environment, favoring the care of children enrolled in the municipal school system, using the development of the integrality of the student. In general, a Multiprofessional Team in the school space provides an expanded look at the students' daily lives, through the search for an education that is not restricted to the transmission of knowledge, cooperating to think and compensate for a need for an education omnilateral.